2015
DOI: 10.1111/jfb.12689
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology and food consumption of fishes in a hypersaline tropical lagoon

Abstract: This study evaluated the trophic ecology (diet composition, trophic strategy, similarities and overlap between species, feeding period and food consumption) of six benthivorous fish species in Araruama Lagoon, the largest hypersaline tropical lagoon on the east coast of South America, with an area of 210 km(2) and an average salinity of 52. The burrfish Chilomycterus spinosus fed on Anomalocardia flexuosa shell deposits, ingesting associated fauna. The caitipa mojarra Diapterus rhombeus differed from all other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…This movement emphasizes the importance of the nursery function of the Tubarão river estuary. Other studies of the Brazilian coast have reported that these species are most abundant as juveniles in estuarine areas of bays (Vilar et al., ), coastal lagoons and mangroves (Almeida‐Silva et al., ; Xavier et al., ) before migration to the coastal zone.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This movement emphasizes the importance of the nursery function of the Tubarão river estuary. Other studies of the Brazilian coast have reported that these species are most abundant as juveniles in estuarine areas of bays (Vilar et al., ), coastal lagoons and mangroves (Almeida‐Silva et al., ; Xavier et al., ) before migration to the coastal zone.…”
Section: Discussionmentioning
confidence: 95%
“…Baltz, Fleeger, Rakocinski, and McCall () showed that salinity had eco‐physiological effects on the growth rates of juveniles, whilst Almeida‐Silva et al. () reported that competition and predation are reduced in hypersaline conditions. Vega‐Cendejas and Santillana () established that high salinity creates an environment that is unfavorable to predators thus allowing tolerant fish species better access to food and space in the upstream gradient in estuaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a hypersaline lagoon in South America, increased food‐web complexity has been related to the stability of hypersaline conditions (Almeida‐Silva et al . , ). Longer‐term research is warranted to better understand the response and recovery of food‐web functioning in hypersaline systems as a result of acute salinity fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…This condition allows ecologically similar species to coexist, and can reduces competition among them (Schoener, 1974;Correa & Winemiller, 2014;Olson et al, 2015). Habitat structure and the daily activities of the species as important factors in determining interspecific interactions may also be considered (Gelós et al, 2010;Carniatto et al, 2012;Almeida-Silva et al, 2015); these aspects were not evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%